Assessment of Poverty among Arable Crop Farmers: A Case Study of Farmers Empowerment Programme (FEP) in Osun State, Nigeria - A. B, Ayanwale; Adisa , O. D (Asian Journal of Agriculture and Rural Development, 2012)
Farmers’ Empowerment has become an important part of the development agenda in the recent years. This study identified and analyzed the poverty status in terms of incidence, depth and severity among arable crop farmers in Osun State and compared the socio-economic characteristics of beneficiaries and non-beneficiaries of Farmers Empowerment Programme (FEP) in Osun State, Nigeria. The study made use of pre-tested and validated structured questionnaire. A multi-stage sampling procedure was used to select 240 respondents. Data collected were analyzed using a combination of descriptive statistics, t-test of difference of two means and p-alpha measures of poverty. The result of poverty incidence, depth, and severity among respondents indicated that poverty incidence was lower among the FEP beneficiaries (0.42) than the non beneficiaries (0.58). Poverty gap index was also lower among the beneficiaries of FEP (0.19) than with the non-beneficiaries (0.46). The severity of poverty was mild (0.13) among the FEP beneficiaries while it was severe among non-beneficiaries (0.43). The Lorenz curve revealed that 22.5 percent of the respondents control 50 per cent of the resources available indicating an apparent inequality in income distribution. A significant difference exists between the age (p<0.05), household size (p < 0.05), membership of cooperative societies (p < 0.05), land ownership (p < 0.05) and income (p < 0.05) of beneficiaries and non-beneficiaries of FEP, respectively. In conclusion, the FEP has alleviated poverty among the participants in the study area. The level of education, household size and farmers’ experience are the key determinants in alleviating poverty among the participating arable crop farmers in the FEP in Osun State.